Practice of Dramatic Performance in Barka Dance - K. C., Durga Lal (Haimaprabha, 2021)
Barka dance is one of the greatest dramatic performances of Tharu Culture. This traditional Tharu dance is performed to keep locals safe from danger and diseases. Barka, which literally translates to ‘big’ in the Tharu language is based on the tales of the Mahabharata and TharuLokMahabharat, Barkimar. The dance, which is carried out from the day of Krishna Janmasthami to Tihar is performed after a long cultural and religious procedure. Condensed versions of this dance are frequently performed during different festivals and fairs. The complete dance requires worshipping different gods and goddesses. They need more than 3o artists to perform the Barka dance. Every character performs a different role according to the story of Mahabharata. They tell the whole story through songs and performance of the characters. It is very important to perform drama in Barka dance for the Tharu community. They learn the message of the story easily watching the performance rather than telling the story. So it is a very traditional practice in the Tharu community. This dance is at risk of extinction because of its time, cost and lack of artists.